Review on impact response of reinforced concrete beams: Contemporary understanding and unsolved problems - Pham, Thong; Chen, Wensu; Hao, Hong (SAGE PUBLICATIONS INC, 2021)
Designing protective reinforced concrete (RC) beams against impact loadings is a challenging task. It requires a comprehensive understanding of the structural response of RC beams subjected to impact loads. Significant research efforts have been spent to unveil the impact response of RC beams by using analytical models, experimental testing, or numerical investigations. However, these studies used various assumptions in the analytical derivations and different test setups in the impact testing, which led to significantly different responses and observations of similar structures and similar loading conditions. For example, a minor change in contact surface can triple the maximum impact force of identical RC beams. This study provides a review of the contemporary understandings of the RC beam responses to impact loads, and explains the different observations and conclusions. Some unsolved issues for protective structures, that is, RC beams to resist impulsive loads are also discussed. It is suggested that future studies should take into consideration the conditions of the test setup, simplifications and assumptions made in analytical derivations for better interpretations of the obtained results.